An evaluation of varying protocols for high‐level disinfection of flexible fiberoptic laryngoscopes. (14th August 2014) - Liming, Bryan; Funnell, Ian; Jones, Anthony; Demons, Samandra; Marshall, Kathryn; Harsha, Wayne
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The use of flexible fiberoptic laryngoscopes (FFLs) is ubiquitous in otolaryngology practices. As with any medical device, there exists a small risk for transmission of pathogenic microorganisms between patients, necessitating high‐level decontamination between uses. Most of the literature to date has studied channeled scopes such as those used in esophagogastroduodenoscopy and colonoscopy. A recent study of nonchanneled flexible laryngoscopes suggested that current high‐level decontamination practices in use at some institutions, including ours, may be overly aggressive. We sought to evaluate and compare the efficacy of varying techniques of high‐level disinfection of FFLs. Study Design FFLs were used in routine clinical encounters and then disinfected with a variety of techniques. The FFLs were then cultured for bacteria and fungi, and the rates of positive cultures were compared between the techniques and the controls. Methods In this study, we took FFLs following use in routine clinical practice and disinfected them using one of eight decontamination protocols. We compared the bacterial and fungal culture results to positive and negative controls. Results We demonstrated that each of the eight cleaning protocols was statistically efficacious at removing bacterial contamination. Our results for fungal cultures did not reach statistical significance. Conclusions Using in vitro inoculation of FFLs, this study demonstrated that quicker and more cost‐effective practices are equally efficacious to more time‐consuming and expensive techniques with regard to bacterial contamination of FFLs. Level of Evidence NA Laryngoscope, 124:2498–2501, 2014